2013
DOI: 10.1111/tri.12073
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal allograft fibrosis by transient elastography

Abstract: SummaryTransient elastography (TE, Fibroscan) has been established as a noninvasive assessment tool of liver fibrosis. We evaluated potentials and limitations of TE for identifying renal allograft fibrosis. The technical possibility of kidney examination by TE was assessed in two 10-week-old German landrace pigs and kidney stiffness (KS) was evaluated in 164 renal transplant patients. KS could be determined in all animals at the pole and pars media (29 AE 10 kPa vs. 31 AE 17 kPa). In human renal allografts KS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 30 publications
3
44
0
1
Order By: Relevance
“…In renal allografts, the two main modalities to assess fibrosis are ultrasound and magnetic resonance imaging (MRI). Ultrasound-based measurement of tissue elasticity (elastography), an approach relatively well established in the assessment of liver fibrosis, has been suggested to correlate with fibrosis in kidney allografts (420)(421)(422)(423)(424), but others have found no such correlation (425). MRI-based elastography is an alternative approach, but the first findings in kidney allografts with fibrosis were disappointing (426).…”
Section: Imagingmentioning
confidence: 99%
“…In renal allografts, the two main modalities to assess fibrosis are ultrasound and magnetic resonance imaging (MRI). Ultrasound-based measurement of tissue elasticity (elastography), an approach relatively well established in the assessment of liver fibrosis, has been suggested to correlate with fibrosis in kidney allografts (420)(421)(422)(423)(424), but others have found no such correlation (425). MRI-based elastography is an alternative approach, but the first findings in kidney allografts with fibrosis were disappointing (426).…”
Section: Imagingmentioning
confidence: 99%
“…linear increase of renal tissue elasticity associated with elevated urinary pressure [22,26]. Gender [21,34], race [27], weight or body mass index (BMI) [20], and also age [23,34,46] can modify the results in US elastography and several studies have found significant variations of renal parenchymal elasticity in these parameters [20,21,23,27,34,46].…”
Section: Ultrasound Elastography In Renal Diseasesmentioning
confidence: 99%
“…Therefore, measurements of the stiffness in the same part of the kidney (subcapsular, cortex and medulla) are advisable to obtain valid and uniform results [20,27] and also establish universal technique standards in the future for reliable and comparable results.…”
Section: Evaluating Fibrosis In Native Kidney With Us Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them were about animals [36][37][38][39][40][41][42] , some of them were about MRI or MR elastography [43][44][45][46][47][48][49][50][51][52] , some of them were about other organ systems [53][54][55][56][57][58][59][60][61][62][63][64][65] , some of them were about elastography technic 28,[66][67][68][69] and some of them were about non elastography related kidney studies 70 . We excluded these articles.…”
Section: Literature Reviewmentioning
confidence: 99%